2014
DOI: 10.1111/jace.13229
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocene‐Catalyzed Growth of Single‐Crystalline 6H‐SiC Nanoribbons

Abstract: Single crystal 6H-SiC nanoribbons were in situ synthesized in large scale on the as-prepared SiC-Si ceramic substrates via a facile heat-treatment approach using ferrocene as catalyst. The as-synthesized nanoribbons were up to several millimeters long, with widths of 200-300 nm and thicknesses of 20-80 nm. A novel combination growth mechanism of vapor-liquid-solidbased and vapor-solid-tip was proposed for the growth mode of the as-synthesized nanoribbons. This study provided not only a new method for synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…According to previous literatures, the possible formation mechanism of SiCnws could be explained as follows. [45][46][47] FeðC 2 H 5 Þ 2ðsÞ ! FeðC 2 H 5 Þ 2ðgÞ…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous literatures, the possible formation mechanism of SiCnws could be explained as follows. [45][46][47] FeðC 2 H 5 Þ 2ðsÞ ! FeðC 2 H 5 Þ 2ðgÞ…”
Section: Resultsmentioning
confidence: 99%
“…According to previous literatures, the possible formation mechanism of SiCnws could be explained as follows. [ 45–47 ] Fe ( C 2 H 5 ) 2 false( normals false) Fe ( C 2 H 5 ) 2 false( normalg false) Fe ( C 2 H 5 ) 2 false( normalg false) Fe ( g ) + 10 normalC ( s ) + 5 normalH 2 false( normalg false) Fe ( g ) Fe ( 1 ) Si ( s ) Si ( g ) 3 normalC ( s ) + normalO 2 false( normals false) 2 CO ( g ) Si ( g …”
Section: Resultsmentioning
confidence: 99%
“…During the pyrolysis of PHC, HfO(g) and HfO 2 (s) would be produced, and the involved reactions were calculated in our previous work . It is reported that HfC nanowires could not be obtained when there is no catalyst‐assisted reaction, and no sign of droplet can be observed according SEM and TEM images (Figures and ), thus the alloy droplet is presumed to be at the bottom of HfC nanowires …”
Section: Resultsmentioning
confidence: 99%
“…17 It is reported that HfC nanowires could not be obtained when there is no catalyst-assisted reaction, 24 and no sign of droplet can be observed according SEM and TEM images (Figures 4 and 6), thus the alloy droplet is presumed to be at the bottom of HfC nanowires. 25 In addition, it can be inferred that only vapor-liquid (VL, V: HfO; L: Fe-C-Hf) and solid-liquid (SL, S: HfO 2 ; L: Fe-C-Hf) interface between seed particles and atoms exists Figure 7B. It is reasonable that atoms could be incorporated into HfC nanowires through the VS and SS interface, which would result in an increase in the diameter.…”
Section: The Growth Of Awl-like Hfc Nanowiresmentioning
confidence: 98%
“…(2) Geometry: Compared with the nanofiller with cylinder geometry, it is easier for the matrix materials to adhere to the nanofiller with a sheet or belt-like geometry. In our previous work, SiC nanoribbons have been synthesized in large-scale using ferrocene as catalyst by a new combination growth mechanism of vapor-liquid-solid-based and vapor-solid-tip [12,13], unlike previously reported one-step vapor-solid growth for SiC nanowires [6] or two-step vapor-solid growth for bamboo-shaped SiC nanowires [14,15]. Provided that SiC nanoribbons are designed to incorporate into the silicon-based ceramic coatings, such as SiC-Si, it can efficiently suppress the cracking of the coatings, which may improve the oxidation inhibition ability of the coated C/C composites.…”
Section: Introductionmentioning
confidence: 99%